Pengaruh Tekanan Pemangku Kepentingan, Intellectual Capital dan Tata Kelola Perusahaan Terhadap Kualitas Laporan Keberlanjutan Pada Perusahaan Yang Tergabung Pada Idx Finance - Iman, Agis Saeful; suripto, Suripto (Jurnal Ilmiah Wahana Pendidikan, 2023)
The study's objective is to comprehend how corporate governance, intellectual capital, and stakeholder pressure affect the standard of sustainability reporting on companies participating in the Idx Finance period from 2018 to 2021. Using the saturation sampling technique, samples from 94 businesses were collected. The statistical analysis strategy used is a narrative one. According to the study's findings, interest party pressure has a detrimental quality of sustainability reporting is affected. Intellectual capital has no bearing on how well sustainability reports are produced. The caliber of the report on sustainability is unaffected by the Company's management.